2022
DOI: 10.3390/pathogens11050493
|View full text |Cite
|
Sign up to set email alerts
|

Differential In Vitro Growth and Cell Killing of Cancer versus Benign Prostate Cells by Oncolytic Parainfluenza Virus

Abstract: The development of effective oncolytic viruses will require understanding the differences in virus replication and killing between normal and cancer cells. Here, we have evaluated infections of metastatic cancer (22Rv1) and benign non-tumorigenic (BPH-1) prostate cell lines with a mutant parainfluenza virus 5 (P/V/F) encoding a defective V protein and a hyperfusogenic F protein. Under low multiplicity of infection (MOI), the P/V/F mutant efficiently spread in 22Rv1 cells but was restricted in BPH-1 cells due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The use of oncolytic viruses contributes to the mechanisms that have evolved over millions of years during the coexistence of humans and viruses [ 52 , 53 ]. Recent research has revealed that some viruses have BH regions that target mitochondrial membrane permeabilization directly or interact with certain Bcl-2 family proteins ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of oncolytic viruses contributes to the mechanisms that have evolved over millions of years during the coexistence of humans and viruses [ 52 , 53 ]. Recent research has revealed that some viruses have BH regions that target mitochondrial membrane permeabilization directly or interact with certain Bcl-2 family proteins ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PIV5 virus PIV5-P/V-CPI− (P/V virus) expressing green fluorescence protein (GFP) was generated, grown, and tittered in Vero cells as described previously [ 19 , 25 ]. For infections, cells were either mock-infected or infected with virus diluted in DMEM supplemented with 10% BSA (Gibco) as described previously [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Supernatant from treated cells was collected at the indicated time points and virus was inactivated by acid treatment followed by neutralization, as previously described [ 24 ]. HEK-Blue IFN-α/β indicator cells (Invivogen) and QUANTI-Blue reagent (Invivogen), were utilized to detect biological levels of IFN-I as per manufacturer’s instructions [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…P/V-CPI- also induced proinflammatory cytokines and caused severe CPE in infected cells, which eventually underwent apoptosis ( Wansley and Parks, 2002 ; Dillon et al, 2006 ). Currently, numerous studies have shown that P/V-CPI- increases the killing effect on tumor cells by promoting the production of double-stranded RNA, activating caspase-dependent death pathways, interfering with the DNA damage repair response in tumor cells, abrogating PKR-mediated protein synthesis, and forming extensive syncytia, etc., ( Wansley et al, 2003 , 2005 ; Dillon et al, 2006 ; Gainey et al, 2008a ; Kedarinath and Parks, 2022 ).…”
Section: Protein Application To Tumor Immunotherapymentioning
confidence: 99%
“…Preliminary studies found that P/V-CPI- was oncolytic and reduced tumor burden in mice. Further research disclosed that P/V-CPI- activated the caspase apoptosis pathway and formed syncytia to kill tumors; surprisingly, it is safe for normal or benign human cells ( Capraro et al, 2008 ; Gainey et al, 2008b ; Kedarinath and Parks, 2022 ). To improve its killing ability, a mutation (G3A) was introduced at the third position of the F protein fusion peptide, resulting in increased fusogenicity and tumor killing through necrosis and inflammatory responses.…”
Section: Protein Application To Tumor Immunotherapymentioning
confidence: 99%